Peningkatan Kemampuan Algebraic Thinking Siswa melalui Pendekatan Contextual Teaching and Learning (CTL) - Laswadi, Laswadi (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
The algebraic thinking ability of junior high school students remains low. This condition is indicated by their limited understanding of story questions. Students lack practice in expressing what is known and asked in story problems. One of the causes of this low algebraic thinking ability is the use of inappropriate learning models or approaches. This research aims to apply the Contextual Teaching and Learning (CTL) approach to enhance students' algebraic thinking skills. The purpose of this study is to determine whether the Contextual Teaching and Learning (CTL) approach can improve students' algebraic thinking skills. The population of this study consists of 77 students from class VIII of MTsN 6 Kerinci. The research sample includes 38 students divided into two groups. The experimental research method is employed in this study. The results indicate that the N-Gain in the experimental group falls within the moderate range, namely 0.55, while the control group's N-Gain falls within the low range, specifically 0.26. The results of the hypothesis test demonstrate that the Contextual Teaching and Learning (CTL) approach significantly improves students' algebraic thinking skills. Hence, it is recommended to implement the Contextual Teaching and Learning (CTL) approach in current instruction to support the enhancement of students' algebraic thinking skills.